The legal status of Tuvan women through the prism of the Laws of the Tuvan People's Republic - Natsak, Organa D. (The New Research of Tuva, 2021)
The article analyzes the evolution of the constitutional, civil and legal status of Tuvan women through the prism of the laws of the Tuvan People’s Republic (TPR), attempts to determine the genesis of certain norms of women-related legislation through a comparative analysis with Soviet legislation. The article also considers social, cultural, and political factors in the life of the Tuvan society. For its sources, the study relies on the constitutions, criminal and civil laws of the TPR, which formed the political and legal basis for the emancipation of Tuvan women.The legislative experience of the USSR was the legal guidance for the TPR, and the Tuvan laws directly borrowed certain norms of Soviet laws. At the same time, the socio-cultural and socio-political specifics of the TPR were also taken into account in the course of lawmaking.The constitutions of the TPR endowed women with political rights, civil liberties, constitutionally guaranteed equality with men, access to government, education, and modern healthcare. However, for the emancipation of women, constitutional recognition of equality with men was not enough. To transform the status and role function of women, to provide political socialization and inclusion of women in the country's economy, it was necessary to add a number of provisions to the criminal and civil laws of the TPR, which thus explains our separate focus on these areas of legislation.Criminal laws of TPR prohibited physical abuse of women, forced and early marriages, and involvement in prostitution. A new form of marriage registration was implemented, as well as contractual and judicial regulation of property relations between spouses in case of divorce, and property relations in case of unregistered cohabitation. Also introduced were the practice of paternity identification and duties of the biological father to a child born out of wedlock. The labor laws of the TPR introduced a differentiated approach to the labor of men and women. Women’s labor received certain benefits due to women's reproductive functions, and made part of industrial relations and the state economy. There finally appears a new type of a working woman, the one enjoying state-guaranteed salary and labor rights.It is concluded that both the Constitutions and the criminal and civil laws of the TPR were the political and legal basis for the emancipation of the Tuvan woman.
Keywords: Tuvan People’s Republic; Tuva; Tuvans; Tuvan history; equal rights; women’s legal status; emancipation; women’s rights